Quranic mushaf use and religious character: A meta-analysis - Ence Oos M. Anwas; Janu Arlinwibowo; Ismail Nur; Juli Susanto; Imam Shah; Miswanto Miswanto; Asep Rifqi Abdul Aziz; Ihsan Maulana Anwas (Research and Social Study Institute, 2025)
This meta-analysis examines the association between use of the Qur’anic mushaf and the development of religious character and Qur’anic literacy. Studies were identified through Google searches and screened against a priori inclusion criteria. Following data extraction, pooled effects were estimated with a random-effects model. The analytic workflow comprised tests of heterogeneity, calculation of the summary effect size, assessment of publication bias, and moderator analyses. Across 33 studies (N = 2,209), the pooled correlation was r = 0.53, indicating a moderate-to-strong association between mushaf reading intensity (including memorization and habitual practice) and positive religious character outcomes—namely religiosity, student character traits, emotional intelligence, and learning behavior. These findings suggest that character-education initiatives should integrate structured Qur’anic literacy within both formal and non-formal settings, supported by equitable access to printed and digital mushaf and sustained guidance from teachers, religious instructors, and parents.